Performance of underwater data transmission using incoherent modulation MFSK in very shallow waters - Jan H. Schmidt; Aleksander M. Schmidt; Iwona Kochańska; Ryszard Studański; Andrzej Żak (International Journal of Electronics and Telecommunications, 2024)
Ensuring universal and stable underwater communication in shallow waters for various environmental conditions is a difficult scientific and engineering task. This applies in particular to underwater communication systems that use acoustic waves in very shallow underwater channels, where multipath propagation permanently occurs. The article provides assumptions for a system working with incoherent M-ary Frequency-Shift Keying (MFSK) modulation, along with guidelines for eliminating the impact of the multipath phenomenon. The results of experimental tests carried out in a lake for two seasons and, therefore, different sound velocity profiles are presented. For comparison purposes, three transducers placed at different depths, including at the bottom of the reservoir, were used to receive the transmitted signals.